Bioecology of Coconut Crab (Birgus latro L.) on Kaledupa Island - Rosnawati, Veni (Universitas Sembilanbelas November Kolaka, 2020)
Bioecology of Coconut crab (Birgus latro L.) On Kaledupa Island, the objective of the research is to know the Biological characteristics (morphometric measurements in the length and width of the carapax, cephlathorax added rostrum (Cp + r) and body weight) and to know the Ecological characteristic (population size) Coconut crab which is on the island of Kaledupa. Sampling technique used the CMRR (Capture-Mark-ReleaseRecapture) method. Data analysis techniques used: (1) Coconut crab morphometry. Data were analyzed descriptively by calculating the average length and width of the carapax, cephalothorax + rostrum length and body weight, (2) Data on sex ratio and population estimation were analyzed quantitatively. Based on the result of the analysis, the highest morphometric measurements are the length of the carapax with an average of 6.37 cm, the width of the carapax 6.03 cm, the length of the cephalothorax + rostrum 10.06 cm, which is located at the location of Station I (Hoga island, Furake sub-village). This is because of this station has unspoiled environmental conditions and there are burrows or caves where the Coconut crab is hiding, where the station belongs to the Wakatobi National Park which is a protected area, and has coconut and other shrub vegetation. These are a food source of Coconut crab s, so this area is ideal for the survival of Coconut crab. The lowest morphometry measurements obtained by carapax length with a mean of 5.62 cm, carapax width of 5.49 cm, length of cephalothorax + rostrum of 9.044 cm, which is found at the location of Station II (Sombano village). This is thought to be the condition of habitats that have been converted into other uses such as the opening of plantation land, so many of the Coconut crab hide outs are damaged. The comparison of male and female sex ratio is 13 Male: 7 Female.